Heparin Neutralizing Activity (HNA) and Antithrombin III in Coronary Artery Disease - Cella, G; Russo, R (Thrombosis and Haemostasis, 1977)
Plasma from 14 patients with severe and diffuse coronary atherosclerosis has been compared with that obtained from a normal control group. While a decreased he parin-thrombin clotting time was demonstrated in the patient group, suggesting an increased level of circulating platelet factor 4, there was no significant alteration in plasma antithrombin III level. These results do not support a recent suggestion of a mild chronic intravascular coagulation in atherosclerosis.